Downlink processing algorithms for multi-antenna wireless communications. - Dakdouki, Ali S. (IEEE Communications magazine)
The recent development of communication theory and radio technology has intensified interest in multi-antenna systems as an effective technique to combat fading of the desired signal, tackle interference from other signals, and increase the data rate in wireless communications. This article provides a survey of downlink processing algorithms for multi-antenna systems. The understanding of fundamental downlink processing strategies is extremely important in analyzing the future of high-capacity/high-quality wireless communications.